Foxp1 expression is essential for sex-specific murine neonatal ultrasonic vocalization - Fröhlich, Henning; Rafiullah, Rafiullah; Abele, Sonja; Rappold, Gudrun (Human molecular genetics, 2017)
Abstract. Autism and speech and language deficits are predominantly found in boys, however the causative mechanisms for this sex bias are unknown. Human FOXP1